2010
DOI: 10.1242/dmm.002311
|View full text |Cite|
|
Sign up to set email alerts
|

Medaka as a model for human nonalcoholic steatohepatitis

Abstract: SUMMARY The global incidence of nonalcoholic steatohepatitis (NASH) is increasing and current mammalian models of NASH are imperfect. We have developed a NASH model in the ricefish medaka (Oryzias latipes), which is based on feeding the fish a high-fat diet (HFD). Medaka that are fed a HFD (HFD-medaka) exhibited hyperlipidemia and hyperglycemia, and histological examination of the liver revealed ballooning degeneration. The expression of lipogenic genes (SREBP-1c, FAS and ACC1) was increased, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
59
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 31 publications
10
59
0
1
Order By: Relevance
“…Several studies have demonstrated that EPA treatment can increase mitochondrial and peroxisomal fatty acid oxidations. In particular, a recent NASH model using Medaka revealed that the administration of EPA mitigated high fat diet-induced disease by restoring normal mitochondrial β-oxidation (Matsumoto et al, 2010), which is confirmed by our findings. Therefore, we conclude that the EPA-mediated reduction of hepatic TG accumulation and attenuation of macrovesicular steatosis at 8 weeks may be attributed to the enhanced mitochondrial and peroxisomal β-oxidations.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Several studies have demonstrated that EPA treatment can increase mitochondrial and peroxisomal fatty acid oxidations. In particular, a recent NASH model using Medaka revealed that the administration of EPA mitigated high fat diet-induced disease by restoring normal mitochondrial β-oxidation (Matsumoto et al, 2010), which is confirmed by our findings. Therefore, we conclude that the EPA-mediated reduction of hepatic TG accumulation and attenuation of macrovesicular steatosis at 8 weeks may be attributed to the enhanced mitochondrial and peroxisomal β-oxidations.…”
Section: Discussionsupporting
confidence: 89%
“…However, according to the proposed pathways for major lipid metabolism (Zhou et al, 2008), the decreased levels of SCD1 and DGAT2 in the HFC diet-fed group might be indicative of mitochondrial dysfunction. Several animal experiments have demonstrated that the administration of EPA improved hepatic steatosis by inhibiting mRNA (Ishii et al, 2009;Kajikawa et al, 2009a,b;Matsumoto et al, 2010) or protein (Tanaka et al, 2010) levels of SREBP-1c and lipogenic enzymes. Although we observed a marked down-regulation of these enzymes at the mRNA level, we failed to observe a significant role for EPA at the protein level.…”
Section: Discussionmentioning
confidence: 99%
“…The lipid-lowering effect of omega-3 in liver is not solely due to acceleration of fatty acid oxidation by PPAR-α activation but due to its effect on other signaling pathways. Moreover, omega-3 regulated the expression of SREBP-1c and FAS ( Figure 4A-B) as supported by other studies [63,64]. The decrease in apoCIII expression is due to the upregulation in PPAR-α expression, thus contributing to the lipid and lipoprotein lowering properties of fish or fish oil intake [65].…”
Section: Discussionsupporting
confidence: 78%
“…Blood samples were collected as described 8 . Fish were kept on ice for 1–2 minutes and then bled by cutting a ventral portion of the tail fin.…”
Section: Methodsmentioning
confidence: 99%
“…It has previously been reported that drug assessment using a HFD-fed medaka model is feasible 8 . However, no studies of the effects of L-carnitine on fatty liver found in this model have been reported.…”
Section: Introductionmentioning
confidence: 99%